Forming Character through Learning Islamic Values in Students: A Study at State Elementary School 085115 Sibolga - Simanjuntak, Fitriyani; Simamora, Merlina; Azizi, Shofiah (MANDAILING GLOBAL EDUKASIA, 2024)
Character strengthening education is one of the targets or goals of education in Indonesia. Various methods are used by educators to create students who are capable and have good character. However, in reality the implementation of character strengthening education does not go as expected. There are various factors that become obstacles in its implementation. This study aims to analyze the mechanism of character formation of students through the instillation of Islamic values ​​in elementary schools. This study is a descriptive qualitative study. The subjects of this study were elementary school students. Research data were collected using interview and observation techniques. The data obtained were analyzed using data triangulation techniques. The results of the study showed that the formation of student character through the instillation of Islamic values ​​was successful. This is because Islamic values ​​are very close to students' daily lives. Based on this, character strengthening education can be carried out with an approach to instilling Islamic values.